Ulayat Land and Agrarian Reform Policy in West Sumatra - Ihsan, Arif; Salim, M. Nazir (Sekolah Tinggi Pertanahan Nasional, 2022)
One of the objects of Agrarian Reform in West Sumatra is the Ulayat Land. The practice is carried out by changing the status of Ulayat Land to state land through the mechanism of release by Niniak Mamak. Ulayat Land is a plot of heritage land and its natural resources obtained from generations as regulated by local governments both in designation and utilization. This study aims to explain why Ulayat Land is used as a Land Object of Agrarian Reform (TORA) in West Sumatra and why the mechanism of giving is individually and not collectively. With qualitative methods, this study analyzes the process and mechanism of assigning TORA Objects sourced from Ulayat Land to their redistribution. This study found that the determination of Ulayat Land to be state land which was then distributed to the Domo Tribe as one of the solutions offered by the Dharmasraya Regency Land Office and approved by the Nagari Customary Density (KAN). This policy is considered the best solution to save the Ulayat Land of the Domo Tribe, West Sumatra. The author concludes, to keep Ulayat Land maintained, the redistribution mechanism can be used to save Ulayat Land because all control is still under indigenous institutions (KAN). Even de jure, these lands have been redistributed to members of indigenous communities.